Laboratory Culture and Maintenance of Stenotrophomonas maltophilia. Issue 1 (6th February 2014) - Mahdi, Osama; Eklund, Bridget; Fisher, Nathan
Abstract: Stenotrophomonas maltophilia is a ubiquitous soil bacterium that is increasingly recognized as an emerging nosocomial pathogen. This unit includes protocols for the in vitro growth and maintenance of S. maltophilia . Curr. Protoc. Microbiol . 32:6F.1.1‐6F.1.6. © 2014 by John Wiley & Sons, Inc.